1979
DOI: 10.1104/pp.63.6.1198
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Genetically Defined Peptidases in Maize

Abstract: The activities of genetically defined amino-and endopeptidases of maize were compared in pericarp, endosperm, and embryonic tissue of the maize kernel from 5 days postpollination until harvest. Activities were highest in the immature stages and declined as drying progressed. The expression of some of the peptidase genes contributed by the pollen parent was examined during early endosperm development in an F1 cross. The paternaly contributed peptidase variants could first be detected 7 days after pollination.Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Enzyme was also significantly cleaved ApNA whereas the activity of enzyme with VpNA was found to be negligible. Results were consistent with previous findings for AP activities in barley (Strelec et al, 2009), with substrate specificities of partially purified maize seed APs (Vodkin and Scandalios, 1979), as well as with AP zymograms of pea (Pisum sativum) seeds (Elleman, 1974). However AP activity with LpNA as substrate decreased during maize seed germination (Vodkin and Scandalios, 1980), this is inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…Enzyme was also significantly cleaved ApNA whereas the activity of enzyme with VpNA was found to be negligible. Results were consistent with previous findings for AP activities in barley (Strelec et al, 2009), with substrate specificities of partially purified maize seed APs (Vodkin and Scandalios, 1979), as well as with AP zymograms of pea (Pisum sativum) seeds (Elleman, 1974). However AP activity with LpNA as substrate decreased during maize seed germination (Vodkin and Scandalios, 1980), this is inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…The proteolytic activity of grains during ensiling remains unknown. It has been reported that protease activities in grains gradually decline during maturation, whereas they drastically increase after germination . These findings suggest that protease activities in grains used as TMR ingredients are low because the grains are well matured and have not germinated.…”
Section: Resultsmentioning
confidence: 94%
“…This finding was inconsistent with the result of the present study, in which LP and MOL+LP in F-FTMR had lower AN and PA NPN contents than the control at 60 d of fermenting. Protease activities are lower when grains are used as TMR ingredients because they are well-matured and un-germinated [ 46 , 47 ]. In the present study, there were no fresh forages but hay, silages, and grains in E-FTMR, and they were not beneficial for microorganisms and protease activities in E-FTMR diets.…”
Section: Discussionmentioning
confidence: 99%